Folate, Vitamin B12, and Homocysteine Levels in Women With Neural Tube Defect-Affected Pregnancy in Addis Ababa, Ethiopia - Kucha, Winner; Seifu, Daniel; Tirsit, Abenezer; Yigeremu, Mahlet; Abebe, Markos; Hailu, Dawit; Tsehay, Dareskedar; Genet, Solomon (Frontiers in Nutrition, 2022)
Background: Neural tube defects (NTDs) are the most prevalent defects associated with pre-pregnancy diet with low levels of maternal folate. They are linked to severe morbidity, disability and mortality as well as psychological and economic burdens. Objective: The goal of this study was to determine the levels of folate, vitamin B12, and homocysteine in the blood of women who had a pregnancy impacted by NTDs. Subjects and Methods: A case-control study was undertaken in women with NTD affected pregnancy. The study comprised a total of 100 cases and 167 controls. Enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of folate, vitamin B12, and homocysteine in serum. Results: We found that 57% of cases and 33.5% of controls had serum folate levels below the cut-off value and 43% of cases and 20.4% of controls had serum vitamin B12 levels below the cut-off value. Twenty-seven percent of cases and 6.6% of controls had hyperhomocysteinemia (HHcy). The median concentrations of folate, vitamin B12 and homocysteine in cases and controls were 4.78 ng/mL and 8.86 ng/mL; 266.23 pg/mL and 455 pg/mL; 13.43 μmol/L and 9.7 μmol/L respectively. There was a statistically significant difference in the median concentration of folate, Vitamin B12 and homocysteine between cases and controls (p < 0.001 in all the three cases). Conclusion: Folate and vitamin B12 are deficient in both case and control mothers. The significantly lower levels of folate and vitamin B12 with an elevated homocysteine levels in NTD affected pregnancy may be an indication that these biochemical variables were risk factors for NTDs. Folate/multivitamin supplementation and/or food fortification should be promoted.